(untitled) (Dhaka University Journal of Science, 2022)
Mixed ligand binuclear complexes of Cu(II) and Cd(II) with adenine (Ade) and 1,4-diazabicyclo[2.2.2]octane (DABCO) have been synthesized at a metal to ligands (M:L:L′) molar ratio of 1:1:1 in aqueous medium under ambient conditions. All synthesized complexes are powdery solids of different colours, slightly soluble in hot water and decompose at high temperature. Characterization of the complexes was accomplished using various analytical techniques, e.g. metal and chloride content analysis, Fourier transform spectrophotometer (FT-IR), UV-visible spectrophotometer, magnetic measurement, and thermal analyses. The metal and chloride contents analyses of the complexes reveal to their stoichiometry [M2Cl2(Ade)2(H2O)2(DABCO)]Cl2 [M = Cu(II) or Cd(II)]. Analytical data suggests that they are homo metal symmetric binuclear complexes comprises of two [MCl(Ade)(H2O)] moieties in between a DABCO molecule is N,N′-bridge bonded. The arrangements of the ligands around the metal centers are essentially tetrahedral involving N(9) of deprotonated imidazole moiety, one Cl- ion, one oxygen from the water molecule and one tertiary N atom from DABCO completing the coordination. Proton migration occurs from N(9) to the N(1) site resulting into a zwitterionic form of adenine, additionally N(3) site of which is hydrogen bonded with the coordinated water molecule. Electrochemical redox behaviour of Cu(II) in presence of adenine and DABCO in the aqueous medium was also studied. It exhibits quasi-reversible one-electron transfer processes. Dhaka Univ. J. Sci. 70(1): 28-33, 2022 (January)